ANALISIS KEBUTUHAN VIDEO PEMBELAJARAN STATISTIKA BERBANTU PROSHOW - Fhela Vhantoria Ningrum (Universitas Muhammadiyah Kotabumi, 2021)
Online learning during the COVID-19 pandemic demands quality learning media. One of the learning media is video. Video quality can be improved by editing and setting after the recording is complete. Interesting video shows can eliminate the boredom of online learning for a long period. Especially in learning statistics that require complicated calculations. The purpose of this study is to analyze the needs of statistical learning videos assisted by proshow. This research method is descriptive exploratory. The data comes from the results of a questionnaire of 32 students of SMPN 7 Kotabumi. The results of the study are that students need learning media in the form of learning videos that are easily accessible and interesting so that statistics are easy to understand. The Proshow application can make learning videos give impressive effects.